1995
DOI: 10.1074/jbc.270.20.11806
|View full text |Cite
|
Sign up to set email alerts
|

Association of p72 with the src Homology-2 (SH2) Domains of PLCγ1 in B Lymphocytes

Abstract: Phospholipase C gamma-catalyzed inositol phospholipid hydrolysis, a critical step in B cell antigen receptor signaling leading to second messenger generation and proliferation, depends upon tyrosine kinase activation. The B cell antigen receptor-associated tyrosine kinases p53/56lyn, p59fyn, p55blk, and p72syk are assumed to participate in receptor-initiated signaling. It is unknown, however, which of these kinases is involved in the tyrosine phosphorylation and resulting activation of phospholipase C gamma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…Substitution of pheuylalanine at Tyr783 of PLCyl also eliminates PtdIns hydrolysis after platelet-derived growth factor stimulation [36]. The cross-linking of B cell receptors promotes the association of ~7 2 "~ with PLCyl [37]. Abrogation of InsP, production in both syk-negative and lyn-negative cells, therefore, may be due to the upstream transducer PLCy that is not activated under the conditions of the ~7 2 " '~ or p53/56"" defect.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of pheuylalanine at Tyr783 of PLCyl also eliminates PtdIns hydrolysis after platelet-derived growth factor stimulation [36]. The cross-linking of B cell receptors promotes the association of ~7 2 "~ with PLCyl [37]. Abrogation of InsP, production in both syk-negative and lyn-negative cells, therefore, may be due to the upstream transducer PLCy that is not activated under the conditions of the ~7 2 " '~ or p53/56"" defect.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, anti-Ig-induced activation of PLC-␥, a direct substrate of Syk (39,40), was unaffected in a Lyn-deficient cell line, DT40Lyn Ϫ , but abolished in a Syk-deficient cell line, DT40Syk Ϫ (26). This result suggested that the anti-Ig-induced activation of PLC-␥ required Syk activation but could occur in the absence of Lyn.…”
Section: Syk Can Be Regulated Via a Lyn-independent Pathway-thementioning
confidence: 99%
“…A good illustration is the enzymes of the PLC␥ family. These molecules probably associate with tyrosine-phosphorylated Syk in activated B cells through a SH2-type interaction 19 and are potential substrates tein deficiency might be found in a much larger panel of patients, given the great heterogeneity of this malignancy, but no clear relationship between the level of Syk protein in cell Shc, 21,22 could also account for most of the band at 145 kDa in Syk precipitates. Whether it is the inositol polyphosphate 5-extracts and the responding or non-responding nature of the cell was found here.…”
mentioning
confidence: 99%